2007
DOI: 10.1128/aac.01440-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of 2,4-Diamino-6-[2-(Phosphonomethoxy)Ethoxy]-Pyrimidine against Multidrug-Resistant Hepatitis B Virus Mutants

Abstract: The susceptibilities of drug-resistant hepatitis B virus (HBV) mutants to lamivudine, adefovir, tenofovir, entecavir, and 2,4-diamino-6-[2-(phosphonomethoxy)ethoxy]-pyrimidine (PMEO-DAPym), a novel acyclic pyrimidine analogue, were assessed in vitro. Most drug-resistant mutants, including multidrug-resistant strains, remained sensitive to tenofovir and PMEO-DAPym. Therefore, the latter molecule deserves further evaluation for the treatment of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
(50 reference statements)
4
25
1
Order By: Relevance
“…The ETV‐resistant level of clone A1+MV seemed to be high, although the essential role of LAM‐resistant mutations to ETV is well known. Moreover, rtL180M/M204V‐associated high‐level resistance to ETV has been reported in patient‐derived strains but not laboratory strains 21. Such high‐level ETV resistance attributable to these mutations may be peculiar to the ETV refractory patient‐derived clone, and other amino acid residues in the RT region or other regions may be associated with this ETV resistance.…”
Section: Discussionmentioning
confidence: 97%
“…The ETV‐resistant level of clone A1+MV seemed to be high, although the essential role of LAM‐resistant mutations to ETV is well known. Moreover, rtL180M/M204V‐associated high‐level resistance to ETV has been reported in patient‐derived strains but not laboratory strains 21. Such high‐level ETV resistance attributable to these mutations may be peculiar to the ETV refractory patient‐derived clone, and other amino acid residues in the RT region or other regions may be associated with this ETV resistance.…”
Section: Discussionmentioning
confidence: 97%
“…ETV displays a unique cross-resistance pattern, with antiviral activity against both LVDr and ADVr HBV. 21,[35][36][37][38] Conversely ETVr HBV is susceptible to ADV and tenofovir. 8,35 This profile suggests a role for ETV as a cornerstone of HBV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is cumulative clinical and published evidence that indicates that TDF has substantial antiviral efficacy against resistant strains of HBV, especially in lamivudine resistance, none of these studies tested the efficacy of TDF against wild-type HBV in NA-naïve patients (7)(8)(9)(10). Several in vitro studies showed almost unaltered or slightly decreased efficacy of TDF against lamivudine-resistant strains of HBV in comparison with that against the wild-type virus (11)(12)(13)(14). Nevertheless, the clinical implications of lamivudine resistance in CHB patients treated with TDF have not been completely elucidated yet.…”
mentioning
confidence: 99%